Star Receipe Restaurant / Alwie Shafiq Muhammad Khairil ... [et al.] - Muhammad Khairil, Alwie Shafiq; Wetrom, Shaferon; Saidi, Jane; Halimin, Irdha Yana; Roslan, Rosshera; Muhammad Khairil, Anna Shaffera; Imon, Hellytah (2013)
The business oriented Restaurant in our country is getting wide and become famous in few place. Because of that reason, our company will attract and impress the local people in Kata Kinabalu with our different specialties from other existing restaurant. The name of our company is Star Receipe which is means that our company will success as the other company and become one of the best restaurant that exist in Kata Kinabalu City ,we also want to extend our experience in managing a restaurant with our knowledge and skills that we have and become a great entrepreneurship. Other than that, the idea of Star Receipe Restaurant is actually to introduce the public about the business that we run with such different concept and unique services. The name 'Star Receipe' is actually refer to us all as the New Entrepreneur who run this business to create awareness to the public that this business is surely "halal" and need no hesitation, and at the same time, 'Star Receipe' have as much as similar sound that we would attract and absolutely catch our customer's heart and will satisfied their wants and needs as a priority. Our restaurant is not only for serve people with variety of Grilled Salmon and beverages, but we prepared those as in unique way and let the local people to try the western food with the worth prices. Some people want something different or new, so we believe our business can attract variety of end buyers in Kata Kinabalu especially the local people. The markets for this business keep increase due to the number of population change from time to time and we also tend to fulfill the demand as well. Star Receipe Restaurant will locate at Imago Shopping Mall Lot G-45, Kata Kinabalu Sabah. This area is strategic because the people especially the workers and staff in the mall will takes their launch or dinner as near to their job place .Thus, people who visit the mall for their specific reason would also can go to our restaurant to try themselves our variety Grilled Salmon and beverages. The target market for our business will be totally for working people, tourist, student and the local people because there is few education center and people who live on that area.